NAVIGATING GEOPOLITICS: PAKISTAN’S ENERGY SOLUTIONS THROUGH CENTRAL ASIAN COLLABORATIONS - Syed Ehsan Ali; Muhammad Shahab (International Journal of Contemporary Issues in Social Sciences, 2024)
The Central Asian states (CAS) - Kazakhstan, Uzbekistan, Turkmenistan, Kyrgyzstan, and Tajikistan - are rich in natural resources but face the challenge of not having direct access to open seas for exporting their goods. Despite not sharing a border with any of the CAS, Pakistan has sought to benefit from these natural resources through initiatives such as TAPI/TKPI and CASA-1000. However, these projects have faced difficulties due to passing through Afghanistan, which poses security challenges. Pakistan is also grappling with a significant energy and circular debt crisis, requiring a cost-effective energy source to meet its energy demands and address the circular debt. The objective of the paper is to identify potential ways to alleviate Pakistan’s energy crisis through collaboration with the Central Asian states. The research methodology used is qualitative, applying thematic analysis to explore the energy potential of the CAS and the benefits of collaboration with them for Pakistan’s energy challenges.